Entrepreneurship and incorporation in the EU - Ruud A. de Mooij; Gaëtan J.A. Nicodème (Center for Economic Studies and ifo Institute (CESifo), 2006)
In Europe, declining corporate tax rates have come along with rising tax-to-GDP ratios. This paper explores to what extent income shifting from the personal to the corporate tax base can explain these diverging developments. We exploit a panel of European data on firm births and legal form of business to analyze income shifting via increased entrepreneurship and incorporation. The results suggest that lower corporate taxes exert an ambiguous effect on entrepreneurship. The effect on incorporation is significant and large. It implies that the revenue effects of lower corporate tax rates - possibly induced by tax competition
Keywords: H25; M13; 330